Commissions and Local Government Reform: Expressed Leadership Identities of Commissioners in Inquiries Proposing Municipal Mergers in Northern Ireland and New South Wales. Issue 2 (April 2017) - Wallis, Joe; Brodtkorb, Tor; Dollery, Brian; MacCarthaigh, Muiris
Abstract : Commissions of inquiry are frequently used as venue‐alteration mechanisms to investigate and "depoliticize" local government reforms. Through the application of a leadership identity framework that examines the judgments commission chairs make during the course of the inquiry, this article explores the roles commission chairs play as interpretive authorities. The judgments that commission chairs make about the scope of stakeholder engagement and whether to adjust the agenda of the inquiry generate four types of leadership identity: conservator, consolidator, advocate, and catalyst. The leadership identity framework is applied to two commissions conducting inquiries into proposed structural reform of local government in two subnational systems: Northern Ireland and New South Wales. The application of the framework reveals that the commission process itself leads to a shift from a conservator to a consolidator leadership identity in both systems, despite their different and distinctive historical, social, and political contexts. Related Articles: Ertas, Nevbahar. 2015 . "Policy Narratives and Public Opinion Concerning Charter Schools ."Politics & Policy 43 (3 ):426 ‐451 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12120/full König, Pascal D., andGeorg Wenzelburger .2014 . "Toward a Theory of Political Strategy in Policy Analysis ."Politics & Policy 42 (3 ):400 ‐430 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12076/full Raile, Eric D., Amber N. W. Raile, Charles T. Salmon, andLori Ann Post .2014 . "Defining Public Will ."Politics & Policy 42 (1 ):103 ‐130 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12063/full Related Media: Sansom, Graham. 2013 . "The Review of Local Government in NSW ."Future of Local Government. https://www.youtube.com/watch?v = AwQvSVqJN0E UK Democracy Live. 2014 . "Northern Ireland ‐ Assembly Passes the Local Government Bill ‐ 8 April 2014."https://www.youtube.com/watch?v = n6YNcrBhx-s